The effect of customer experience and brand image on customer loyalty on the use of delivery services PT. POS Indonesia - Rifqi Aulia Ahmad; Terra Saptina Maulani (Universitas Negeri Padang, 2022)
This study aims to find out the effect of customer experience and brand image on customer loyalty in the delivery service of PT. POS in Bandung. The research method used is descriptive and verification methods with a quantitative approach, collecting data through distributing questionnaires to 100 respondents with the calculation of determining the sample using the Cochran formula. The statistical analysis instrument used validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test, and f test with the help of SPSS version 25 software. The results showed that partially and simultaneously customer experience and brand image have a significant influence on customer loyalty in the delivery service of PT. POS in the city of Bandung by contributing 62.3% to customer loyalty, while for 37.7% influenced by other factors not examined.